Conversational Agents and Natural Language Interaction 2011
DOI: 10.4018/978-1-60960-617-6.ch018
|View full text |Cite
|
Sign up to set email alerts
|

Future Trends for Conversational Agents

Abstract: In the last decades, there has been a great evolution in the field of Conversational Agents. Currently, there are agents to assist the navigation in Web pages, support elder users when interacting with some computer application to remind them which medicines they should take during the day, or to enhance the learning process by allowing students to review with systems that adapt themselves to their previous knowledge and rhythm of study. In this chapter, the goal is to provide a summary of the future trends th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It is advisable to follow a UCD to adapt the design of the PCA to the needs of the students, which could be the key to overcome many limitations found (i.e., interaction modalities, specific domains, limited language interaction, etc.). It is not the same to design an agent for little children than for High School or University students [39,53,59,62].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is advisable to follow a UCD to adapt the design of the PCA to the needs of the students, which could be the key to overcome many limitations found (i.e., interaction modalities, specific domains, limited language interaction, etc.). It is not the same to design an agent for little children than for High School or University students [39,53,59,62].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the fifth criterion would be: The sixth criterion is the adaptative-evolution possibilities. It has been included from the inspiration of reading the work of Liebermen [55], in which he claimed that autonomous agents can show adaptive and evolution possibilities, i.e., the agent adapts its behavior to each student, and learns how to evolve to interact better depending on previous interactions [56][57][58][59]. PCAs may not have either adaptive or evolution possibilities as in 6.1, to have adaptive possibilities to modify their dialogue and/or gestures to the student as in 6.2, to have evolution possibilities and to learn from the previous sentences of the dialogue to generate different interactions (verbal and or non-verbal) as in 6.3, and even to have adaptive and evolution possibilities so that from the learning of previous and present interactions the behavior and/or dialogue of the agent changes as in 6.4.…”
Section: Human-computer Interaction Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different PCAs applied to different domains and to develop competences from Pre-Primary to Higher Education [39] , [40] . Some domains in which PCAs have been used successfully are: Science [36] , Math [41] , Languages [42] , Storytelling [43] , Social skills [44] , Operating Systems [45] and Programming [46] for Higher Education in object-oriented languages such as C++ [47] and JAVA [48] , [49] , procedural languages such as C [50] , database management such as SQL [51] and the tangible programming Tern in Museums [52] , [53] .…”
Section: Related Workmentioning
confidence: 99%
“…Learning companions can also be considered as a subtype of PCAs in which the emphasis is on the companion role of the agent, in an individual or collaborative use [62] in contrast to agents in which the main role is a teacher or even a student role [39] . Studies have shown that conversational agents acting as educational companions or tutors can facilitate learning [63] , [64] .…”
Section: Related Workmentioning
confidence: 99%